Combining Insurance, Contingent Debt, and Self-Retention in an Optimal Corporate Risk Financing Strategy - Gurenko, Eugene; Mahul, Olivier (World Bank, Washington, DC, 2014)
The authors provide a conceptual framework for designing a comprehensive risk financing strategy for a firm, using an optimal combination of three instruments: self-retention, contingent debt, and insurance. Using an original conceptual model, the risk management decisions of the firm are first decomposed into two sets-choosing attachment points for each layer of financing used in the overall risk financing structure, and, then determining optimal risk allocation arrangements within each layer of risk. This model allows the authors to show how these optimal risk financing arrangements are driven by the costs of risk management instruments, the risk characteristics, and the firm's borrowing constraints. Finally, the authors provide an original perspective to think about optimal ex ante risk management strategies, based on a combination of insurance, savings, and credit at the microeconomic or macroeconomic levels.